Acoustic generation of underwater cavities - Comparing modeled and measured acoustic signals generated by seismic air gun arrays - Khodabandeloo, Babak; Landrø, Martin; Hanssen, Alfred (The Journal of the Acoustical Society of America, 2017)
Source at http://dx.doi.org/10.1121/1.4979939 Underwater vapor cavities can be generated by acoustic stimulation. When the acoustic signals from several air guns are reflected from the sea surface, the pressure drop at some locations is sufficient for cavity growth and subsequent collapse. In this paper the generation of multiple water vapor cavities and their collapses are numerically modeled and the results are validated by comparing with field data from a seismic air gun array test. In a first modeling attempt where cavity interaction is neglected, a correspondence between measured and modeled data is found. Then, this correspondence is improved by assuming that the acoustic signal generated by the other cavities changes the hydrostatic pressure surrounding each cavity. This modeling can be used to estimate the amount and strength of high frequency signals generated by typical marine air gun arrays, given that a calibration step is performed prior to the modeling.